Influence of Dual-layer and Triple-layer Remote Phosphor Package on Optical Properties of White LEDs - Nguyen Thi Phuong Thao; Nguyen Doan Quoc Anh; Kamil Postava; Miroslav Voznak; Phan Xuan Le (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
In this paper, the influence of the distance between phosphor layers in the dual-layer and triple- layer remote package on luminous flux and color rendering property is presented and analyzed. During the simulation, it is recognized that an appropriate distance can produce higher quality of the multi-chip white LED (MCW-LEDs) through adjusting the distance between two and three phosphor layers. According to the research results, 0.1mm is the outstanding distance between two phosphor layers so that the performance of MCW-LEDs can be accomplished the best optimal effect. In addition, the simulation results show that the dual-layer structure yielded higher optical properties than the triple-layer structure in relation to the distance. The highest lumen output of triple layer-structure can be achieved at the distance of 0.6 mm and dual-layer structure is 0.1 mm. Meanwhile, the color rendering index (CRI) changes insignificantly when the distance increases. Triple layer package is not practical for high power white LEDs due to high cost and low conversion efficiency. Dual-layer remote phosphor package with the distance between two phosphor layers of 0.1mm is an optimal structure of LEDs in improving the luminous efficiency and the color quality.